2013
DOI: 10.1088/0004-637x/766/1/57
|View full text |Cite
|
Sign up to set email alerts
|

Outflow Versus Infall in Spiral Galaxies: Metal Absorption in the Halo of NGC 891

Abstract: Gas accreting onto a galaxy will be of low metallicity while halo gas due to a galactic fountain will be of near-solar metallicity. We test these predictions by measuring the metal absorption line properties of halo gas 5 kpc above the plane of the edge-on galaxy NGC 891, using observations taken with HST/STIS toward a bright background quasar. Metal absorption lines of Fe II, Mg II and Mg I in the halo of NGC 891 are clearly seen, and when combined with recent deep H I observations, we are able to place const… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…3.5.5 for possible caveats). Dust inferred using this method has been reported in the Milky Way Fermi Bubbles (Savage et al 2017), the galactic fountain of NGC 891 (Bregman et al 2013;Qu et al 2019), some DLAs at z 1 (Péroux et al 2006;Rahmani et al 2016), and a few z 1.5 LLS with N H 10 19 − 10 20 cm −2 ("sub-DLAs"; Meiring et al 2009a, b), although not all of them (e.g., Quiret et al 2016). On the other hand, dust depletion in z 1 LLS with N H < 10 19 cm −2 has been found to be modest, largely consistent with dust-free gas (e.g., Lehner et al 2013Lehner et al , 2019.…”
Section: Dust Componentmentioning
confidence: 99%
“…3.5.5 for possible caveats). Dust inferred using this method has been reported in the Milky Way Fermi Bubbles (Savage et al 2017), the galactic fountain of NGC 891 (Bregman et al 2013;Qu et al 2019), some DLAs at z 1 (Péroux et al 2006;Rahmani et al 2016), and a few z 1.5 LLS with N H 10 19 − 10 20 cm −2 ("sub-DLAs"; Meiring et al 2009a, b), although not all of them (e.g., Quiret et al 2016). On the other hand, dust depletion in z 1 LLS with N H < 10 19 cm −2 has been found to be modest, largely consistent with dust-free gas (e.g., Lehner et al 2013Lehner et al , 2019.…”
Section: Dust Componentmentioning
confidence: 99%
“…Its ionisation source is not yet well understood, but is generally compatible with photoionisation by radiation from stellar sources (O and B stars, but possibly also hot evolved stars), filtered and hardened by photoelectric absorption by gas in the disc. Study of the DIG in external galaxies remains difficult because of its low surface brightness, however extensive work on edge-on galaxies (see for example the prototype case of NGC 891 as studied in Rand et al 1990;Rossa et al 2004;Bregman et al 2013) has demonstrated that DIG emission is detectable up to several kpc from the disc midplane.…”
Section: The Role Of Diffuse Ionised Gas (Dig)mentioning
confidence: 99%
“…For example, the gas expelled from the galaxy tends to escape in the direction perpendicular to the galaxy plane; therefore, motions in the plane of the galaxy favor the inflow interpretation (e.g., Bouché et al 2013;Combes 2014). As we discuss above, cosmic web inflows are expected to be metal poor so metal-rich moving gas is commonly interpreted as outflow rather than inflow (Lehner et al 2013;Bregman et al 2013). A third possibility is using the relative velocity as a discriminant.…”
Section: Expected Observational Propertiesmentioning
confidence: 99%